AM Fungi Alleviate Phosphorus Limitation and Enhance Nutrient Competitiveness of Invasive Plants via Mycorrhizal Networks in Karst Areas - Shen, Kaiping; Cornelissen, J. Hans C.; Wang, Yongjian; Wu, Changbang; He, Yuejun; Ou, Jing; Tan, Qiyu; Xia, Tingting; Kang, Liling; Guo, Yun; Wu, Bangli (Frontiers in Ecology and Evolution, 2020)
Eupatorium adenophorum is an alien species that threatens community stability and diversity in karst areas. Arbuscular mycorrhizal (AM) fungi form interconnected mycorrhizal network, connecting adjacent plants and plant species. How mycorrhizal networks affect the competition for nutrients between invasive and native plants in karst habitat remains unclear at present. An experiment was conducted using a compartmental growing device, which was composed of two planting compartments (for the invasive E. adenophorum or native Artemisia annua) and a competitive compartment (for the interconnected mycorrhizal network). The experiment contained mycorrhizal fungus treatments, with AM fungi (M+) and without AM fungi (M-) using the species Claroideoglomus etunicatum, and the nutrient utilization treatments using nylon mesh to interconnective mycorrhizal networks, including common utilization (Cu), single utilization (Su) and non-utilization (Nu). The results showed as follows: AM fungi differentially increased biomass, nitrogen (N) acquisition and phosphorus (P) acquisition and significantly reduced N/P ratio of the invasive E. adenophorum and native A. annua under Cu, Su and Nu conditions. Additionally, the biomass, N acquisition and P acquisition of E. adenophorum was greater than A. annua and the N/P ratio of E. adenophorum was significantly lower than A. annua under Cu condition, which AM fungi promoted the accumulation of biomass, N and P for E. adenophorum and A. annua, and E. adenophorum experienced a greater reduction of P limitation than A.annua via the interconnected mycorrhizal network. In conclusion, we suggest that AM fungi endow invasive plants greater alleviation of P limitation and enhancement of nutrient competition than native plants via mycorrhizal network in low-P karst soil.